Improving wheat (Triticum aestivum L.) antioxidative defense mechanisms against salinity stress by exogenous application of potassium silicate - Feghhenabi, Faride (2022)
The primary objective of this study was to investigate the beneficial effects of seed priming and foliar spray of potassium silicate on antioxidant activities under different salinity levels, thereby potentially improving wheat growth. Seeds were soaked into solutions containing potassium silicate (K2SiO3, 1.5 mM) for 6 h, while foliar spray with K2SiO3 (4 mM) was applied at the early and the late stages of tillering. Lake Urmia water was used to prepare salinity levels of 0, 3, 5, 8, 10, 12, and 14 dS m −1. For such traits as anthocyanin, catalase, ascorbate peroxidase, guaiacol peroxidase, and superoxide dismutase activity, an initial increase was observed at lower salinity levels; higher salinities subsequently decreased these traits or they remained mostly constant. Salinity also increased phenol, malondialdehyde, hydrogen peroxide, and polyphenol oxidase, but decreased flavonoid, nitrate content, and nitrate reductase activity. Seed priming and foliar spray provided effective approaches to reduce reactive oxygen species (ROS) manifestation in wheat grown under saline conditions. The improved antioxidant defense abilities by seed priming and foliar spray alleviated the oxidative damage of proteins and lipids and improved nitrate content and nitrate reductase activity.